2002
DOI: 10.1364/ol.27.000046
|View full text |Cite
|
Sign up to set email alerts
|

157-nm coherent light source as an inspection tool for F_2 laser lithography

Abstract: We have developed a 157-nm coherent light source by two-photon resonant four-wave mixing in Xe, with two tunable single-mode 1-kHz Ti:sapphire laser systems at 768 and 681 nm. This light source has been developed to determine the instrumental function of a vacuum ultraviolet spectrometer and to evaluate optical designs for ultra-line-narrowed F(2) laser lithography. The spectral linewidth of the source was less than 0.008 pm (FWHM), with an average power of 0.6 mW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…High-power, high repetition rate Ti:sapphire lasers have been developed in the central gain region around 800 nm [8,9,10]. However the Ti:sapphire laser with an output above 10 W, a repetition rate of 6 kHz, and single mode at the edge wavelength have not yet been developed, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…High-power, high repetition rate Ti:sapphire lasers have been developed in the central gain region around 800 nm [8,9,10]. However the Ti:sapphire laser with an output above 10 W, a repetition rate of 6 kHz, and single mode at the edge wavelength have not yet been developed, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, vacuum ultraviolet (VUV) light sources have extensive applications in various fields such as photolithography [6] and spectroscopy [7]. Sources of VUV radiation are currently limited to excimer lasers [8] and nonlinear methods using frequency mixing in gases [9,10] metal vapors [11], and nonlinear crystals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Togashi et al reported an all-solidstate tunable Ti:sapphire laser system, which consists of an oscillator and three-stage amplifier, to produce a laser with power of 32 W and linewidth of 0.7 GHz at a repetition rate of 5 kHz, and its frequency conversion to vacuum UV radiation in 2001 [8]. A single-mode Ti:sapphire oscillator-amplifier system pumped by three external synchronized sources was developed by Suganuma et al, in which generation of a coherent light source at 157 nm is obtained, the linewidth of the output laser is compressed to 28.3 MHz by a dispersive component in the oscillator, and the output power is 8.5 W by following a four-pass amplifier [9]. In 2007, Hannemann et al reported a narrow-bandwidth injection-seeded self-synchronized Ti:sapphire oscillatoramplifier system at 10 Hz, in which the maximum energy of pulses is 41 mJ with a linewidth of 45.5 MHz and a tunable wavelength range of 764 to 856 nm [10].…”
Section: Introductionmentioning
confidence: 99%